Doubly disabled: diabetes in combination with an eating disorder. Issue 839 (September 1995) - Ward, A.; Troop, N.; Cachia, M.; Watkins, P.; Treasure, J.
Abstract : We present a series of patients with both an eating disorder and diabetes mellitus and compare these to a group of non-diabetic patients from the same clinic. Significantly more of the diabetic patients had previous attempts at treatment for their eating disorder. A high incidence of diabetic complications was noted with clear implications, both clinically and economically, for early intervention. The incidence of childhood trauma was lower in the diabetic than the non-diabetic group. In the majority of patients, diabetes developed before the eating disorder, suggesting that diabetes itself may provide the vulnerability and increase the risk of developing an eating disorder. Early intervention in diabetic clinics may prevent the development of serious eating disorders.